2020
DOI: 10.1107/s2053229620000947
|View full text |Cite
|
Sign up to set email alerts
|

C—Br...S halogen bonds in novel thioureaN-oxide cocrystals: analysis of energetic and QTAIM parameters

Abstract: S, (II), crystallize in the monoclinic space group P2 1 /c. In the crystals, molecules of both components are linked by N-HÁ Á ÁO hydrogen bonds, creating R 2 1 (6) synthons. The bromine substituent of the N-oxide component in (II) is a centre for C-BrÁ Á ÁS halogen bonding to the thiourea molecule. Computations based on quantum chemistry methods (quantum theory of atoms in molecules, QTAIM) and atoms in molecules (AIM) theory were performed for a more detailed description of the observed type of halogen-bondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Moreover, they also explain synergistic effects causing stabilization of molecular structures [39,40]. Despite a growing number of studies on co-crystal structures, including X-ray [41][42][43], NMR, and IR spectroscopy [35], knowledge about the cooperative and competitive behaviour of halogen and hydrogen bonds is insufficient and requires expansion. The halogen and hydrogen bonds exhibit numerous similarities, which has already been described in many theoretical studies [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they also explain synergistic effects causing stabilization of molecular structures [39,40]. Despite a growing number of studies on co-crystal structures, including X-ray [41][42][43], NMR, and IR spectroscopy [35], knowledge about the cooperative and competitive behaviour of halogen and hydrogen bonds is insufficient and requires expansion. The halogen and hydrogen bonds exhibit numerous similarities, which has already been described in many theoretical studies [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The comparative distances and angles of the detected and previously reported halogen bonds are summarized in Table 2 . The intermolecular halogen bonds (C=S⋯Br) between achiral substrates, e.g., thiourea and 3-bromopyridine- N -oxide ( 3 , CCDC1979836) or trithiocyanuric acid and 3-bromopyridine- N -oxide ( 4 , CCDC2011097) have been previously reported [ 41 , 42 ]. The halogen bond in 3 is oriented orthogonally toward the thiocarbonyl plane [the torsion angle of N-C=S⋯Br is 99.88°] like ( P )- 2a , while the torsion angle of N-C=S⋯Br in 4 was 50.95° and −55.90°.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction in Scheme 1 is the first example of the conversion of optically active N-C axially chiral amides to thioamide analogues. The sulfur atom of the C=S group is also known to work as a Lewis base in the halogen bond [ 36 , 37 , 38 , 39 , 40 , 41 ], while it is less commonly studied in comparison with halogen bonding with C=O and C=N functional groups. We were curious about whether the chirality-dependent halogen bond detected in 1a and 1b is also observed in crystals of the thione analogues 2a and 2b .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 More information about the application, co-crystal synthesis and interactions of these three chemical species, as well as various theoretical studies, can be found in our earlier works. [12][13][14][15][16][17] These previous papers also include a search for thiourea and trithiocyanuric acid crystals in the Crystal Structure Database (CSD). 18 The search revealed only a few depositions of para-and ortho-mercaptopyridines, two of which were crystals of pure 4-mercaptopyridine (refcode: AKOVOL; 19 AKOVOL01; 20 AKOVOL02; 21 AKOVOL03; 21 AKOVOL04 (ref.…”
Section: Introductionmentioning
confidence: 99%